Calpain inhibitor I reduces colon injury caused by dinitrobenzene sulphonic acid in the rat. Issue 4 (1st April 2001) - Cuzzocrea, S; McDonald, M C; Mazzon, E; Mota-Filipe, H; Centorrino, T; Terranova, M L; Ciccolo, A; Britti, D; Caputi, A P; Thiemermann, C
Abstract : BACKGROUND AND AIMS: Inflammatory bowel disease is characterised by oxidative and nitrosative stress, leucocyte infiltration, upregulation of expression of intercellular adhesion molecule 1 (ICAM-1), and upregulation of P-selectin in the colon. The aim of the present study was to examine the effects of calpain inhibitor I in rats subjected to experimental colitis. METHODS: Colitis was induced in rats by intracolonic instillation of dinitrobenzene sulphonic acid (DNBS). RESULTS: Rats experienced haemorrhagic diarrhoea and weight loss. Four days after administration of DNAB, the mucosa of the colon exhibited large areas of necrosis. Neutrophil infiltration (determined by histology as well as by an increase in myeloperoxidase activity in the mucosa) was associated with upregulation of ICAM-1 and P-selectin as well as high tissue levels of malondialdehyde. Immunohistochemistry for nitrotyrosine and poly (ADP-ribose) polymerase (PARP) showed intense staining in the inflamed colon. Staining of sections of colon obtained from DNBS treated rats with an anti-cyclooxygenase 2 antibody showed diffuse staining of the inflamed tissue. Furthermore, expression of inducible nitric oxide synthase was found mainly in macrophages located within the inflamed colon of DNBS treated rats. Calpain inhibitor I (5 mg/kg daily intraperitoneally) significantly reduced the degree of haemorrhagic diarrhoea and weight loss caused by administration of DNBS. Calpain inhibitor I also caused a substantial reduction in (i) degree of colon injury, (ii) rise in myeloperoxidase activity (mucosa), (iii) increase in tissue levels of malondialdehyde, (iv) increase in staining (immunohistochemistry) for nitrotyrosine and PARP, as well as (v) upregulation of ICAM-1 and P-selectin caused by DNBS in the colon. CONCLUSION: Calpain inhibitor I reduces the degree of colitis caused by DNBS. We propose that calpain inhibitor I may be useful in the treatment of inflammatory bowel disease.